Food Labels Use Is Associated with Higher Adherence to Mediterranean Diet: Results from the Moli-Sani Study - Bonanni, Americo E. (MDPI, 2013)
Mediterranean diet (MD) has been associated with lower risk of ischemic cerebro- and cardio-vascular disease, neurological degenerative disease, and breast and colonrectal cancers. Nevertheless, adherence to this pattern has decreased. Food labels are a potentially valid means to encourage towards healthier dietary behavior. This study, conducted on a subsample of 883 subjects enrolled in the Moli-sani Project, evaluated whether food labels reading (LR) is associated with MD adherence. Participants completed a questionnaire on nutrition knowledge, information, and attitudes, with a specific question on food labels reading. Biometric measurements, socio-economic status, education, physical activity, and smoking habits were collected. The European Prospective Investigation into Cancer and Nutrition (EPIC) food frequency questionnaire was used to collect dietary habits, and subsequently evaluated by both the Mediterranean diet score (MDS) and Italian Mediterranean index (IMI), a priori dietary patterns. Food consumption patterns were generated by Principal Components Analysis (PCA), an a posteriori approach. Multivariable odds ratios were calculated to quantify the association of LR categories with dietary habits. LR was significantly associated with greater adherence to both MDS (p = 0.0004) and IMI (p = 0.0019) in a multivariable model. LR participants had 74% (MDS) or 68% (IMI) higher probability to be in the highest level of adherence to Mediterranean diet-like patterns. Moreover, they showed greater adherence to Mediterranean-like food consumption patterns (0.1 vs. −0.2, p < 0.0001) and lower adherence to two Western-like patterns (0.01 vs. 0.2, p = 0.009 and 0.1 vs. 0.2, p = 0.02). These findings support an association between food label use and consuming a Mediterranean-type diet.